Qualitative Analysis of Residents′ Perceptions of Tourism Impacts on Historic Districts: A Case Study of Nanluoguxiang in Beijing, China. Issue 1 (1st January 2017) - Dai, Linlin; Wang, Siyu; Xu, Jun; Wan, Li; Wu, Bihu
Abstract : Tourism is becoming a viable and important economic development strategy in the regeneration of historic districts. Nonetheless, tourism may bring negative impacts to the local communities. As a result, local residents′ perceptions and attitudes toward tourism development are critical to the sustainable development of tourism. This study follows a qualitative research approach, attempting to examine the relationship between local residents′ social-demographic features and their perceptions of tourism development. The framework is applied to the case of Nanluoguxiang in Beijing, China, which is a typical tourism destination benefitting from its traditional urban forms. Data from 24 in-depth interviewees are analyzed using word-frequency analysis through text encoding. The results reveal that the cultural perception of the residents promoted place attachment, which was associated with impact perception, and together, they determined behavioral demand. The stronger the cultural perception of the residents is and the stronger their place attachment is, the more the negative impact of tourism is perceived and the stronger their demand for cultural protection is. Long-term residents, those with occupations unrelated to tourism, and those who live adjacent to the tourism attractions perceived more negative impacts.